2016
DOI: 10.1038/srep34382
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging reveals improved Kupffer cell-mediated phagocytosis as a mode of action of glycoengineered anti-CD20 antibodies

Abstract: Anti-CD20 monoclonal antibodies (mAbs) represent an effective treatment for a number of B cell malignancies and autoimmune disorders. Glycoengineering of anti-CD20mAb may contribute to increased anti-tumor efficacy through enhanced antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis (ADP) as reported by in vitro studies. However, where and how glycoengineered Ab may potentiate therapeutic responses in vivo is yet to be elucidated. Here, we have performed mouse liver transplants to demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…The primary in vivo mechanism of cellular cytotoxicity of circulating CD20 mAb-opsonized cells in mice is ADCP by fixed macrophages in the liver (13)(14)(15)17). However, limited data on human in vivo CD20 mAb-mediated cellular cytotoxicity of circulating or tissue resident B cells are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary in vivo mechanism of cellular cytotoxicity of circulating CD20 mAb-opsonized cells in mice is ADCP by fixed macrophages in the liver (13)(14)(15)17). However, limited data on human in vivo CD20 mAb-mediated cellular cytotoxicity of circulating or tissue resident B cells are available.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that natural killer (NK) cells are the primary peripheral blood effector cells performing ADCC, whereas monocytes and neutrophils have minimal cytotoxic activity (10,11). In contrast, in vivo murine studies of CD20 mAb-mediated clearance of circulating B cells show a major role for ADCP by fixed hepatic macrophages (Kupffer cells), with minimal NK cell-mediated cytotoxicity (12)(13)(14)(15)(16)(17). These data suggest that clearance of opsonized B cells could be similar to that of autoantibody opsonized blood cells, which are efficiently cleared by ADCP in the liver and spleen in human autoimmune hemolytic anemia and immune thrombocytopenia (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of many of these mAb is primarily mediated by the innate immune system . More recently, the use of intravital imaging and macrophage depletion strategies have revealed that ADCP by tissue‐resident macrophages, particularly Kupffer cells in the liver, are the major mediator of the therapeutic effect of these drugs, especially when used to treat B‐cell malignancies .…”
Section: The Role Of Macrophages In Host Cell Clearancementioning
confidence: 99%
“…Exhaustion in the context of ADCP has been modeled in vitro using human monocyte‐derived macrophages cultured in the presence of excess numbers of IgG‐opsonized lymphocytes. Under these conditions, maximal clearance is achieved after 4 h, with very little additional engulfment beyond this time . Moreover, the presence of excess IgG‐opsonized lymphocytes on macrophages for 24 h leads to a sharp decrease in their phagocytic activity upon refeeding with fresh targets compared to previously unfed macrophages .…”
Section: Regulating the Phagocytic Capacity Of Macrophages In Efferocmentioning
confidence: 99%
“…In order to understand the contribution of tissue-resident versus bone marrow-derived macrophages for cytotoxic antibody activity (e.g. IgG-mediated B cell depletion in the liver), 31 he and colleagues designed a model system involving chimeric mice expressing organ-specific FcγR. When organ-resident FcγR ± macrophages were depleted by clodronate liposomes, repopulation of the liver by Kupffer cells was observed to be bone marrow-dependent.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%